2017
DOI: 10.1002/jat.3493
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics of pristine and functionalized graphene

Abstract: Graphene-based nanomaterials have received significant attention in the last decade due to their interesting properties. Its electrical and thermal conductivity and strength make graphene well suited for a variety of applications, particularly for use as a composite material in plastics. Furthermore, much work is taking place to utilize graphene as a biomaterial for uses such as drug delivery and tissue regeneration scaffolds. Owing to the rapid progress of graphene and its potential in many marketplaces, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The PG used in this study exhibited characteristics consistent with the manufacturer's technical details with a low oxygen content (~2.5%) and dimensions of 1‐1.2 nm thick and <10 μm lateral dimensions. By our own analysis as reported previously (Bourdo et al, ; Majeed et al, ), it was determined by X‐ray photoelectron spectroscopy that the PG exhibited an elemental composition of about 97% C and 2.5% O. The lateral size of the PG was between approximately 50 and 1750 nm, while a thickness of ~2 nm for the thinnest sections was observed.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The PG used in this study exhibited characteristics consistent with the manufacturer's technical details with a low oxygen content (~2.5%) and dimensions of 1‐1.2 nm thick and <10 μm lateral dimensions. By our own analysis as reported previously (Bourdo et al, ; Majeed et al, ), it was determined by X‐ray photoelectron spectroscopy that the PG exhibited an elemental composition of about 97% C and 2.5% O. The lateral size of the PG was between approximately 50 and 1750 nm, while a thickness of ~2 nm for the thinnest sections was observed.…”
Section: Resultssupporting
confidence: 72%
“…The unmodified PG as used in this study had been extensively characterized by multiple instrumental techniques revealing their physicochemical properties by Majeed et al (Majeed et al, ) and Bourdo et al (Bourdo et al, ). The PG used in this study exhibited characteristics consistent with the manufacturer's technical details with a low oxygen content (~2.5%) and dimensions of 1‐1.2 nm thick and <10 μm lateral dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…Upon chemical treatment (Majeed et al, 2016), functionalized graphene was decorated with some hydrophilic alcohol and carboxylic acid groups, that rendered them less hydrophobic and had fewer large clusters. X-ray photoelectron spectroscopy analysis (Majeed et al, 2016;Bourdo et al, 2017) demonstrated a~6.63 ± 0.14% oxygen content increase compared to~2.5% for initial graphene powder. Graphene oxide (≤ 46% of oxygen, manufacturer data, Suppporting Information Table 1) was finely dispersed in water and formed a stable suspension in water without any significant precipitation observed over more than 2 years of shelf storage.…”
Section: Graphene-based Nanomaterialsmentioning
confidence: 94%
“…Low-and high -oxygen graphene sample preparation. The low-and high-oxygen graphene samples were prepared according to previously reported methods [18,21,36].…”
Section: Methodsmentioning
confidence: 99%